Professor Vanda Zaborskaitė: Why Classic? - Čiočytė, Dalia (Literatūra, 2023)
Vanda Zaborskaitė (1922–2010) was a famous literary critic and the author of a fundamental monograph about the prominent Lithuanian poet Jonas Mačiulis-Maironis (Maironis, 1968, 1987). Vanda Zaborskaitė wrote during the period of Soviet occupation, when Marxist criticism was obligatory. She used the sociological method as interpreted by Marxism, but she never accepted its philosophical determinism. She considered it important to put a literary work in the contextual frame of the literary history; however, she did not accept the view according to which literature is ruled by the laws of the social and cultural history. The philosophical position of Vanda Zaborskaitė was modernisation of the classical literary criticism, which is a tradition of the literary study sourced from the times of Aristotle’s Poetics. A characteristic of this tradition is reliance on the deep ordered structures observed in literary works. Vanda Zaborskaitė investigated such deep literary structures (images and their constellations) as codes of individual artistic self-awareness. In the opinion of the researcher, the pinnacles of literary art are those works which, by employing aesthetic persuasion, interpret the classical ideas of the Western world: the ideas of the absolute value of the personality, freedom, and the primate of the spirit. Professor Vanda Zaborskaitė researched the Lithuanian classic authors during the years of Soviet occupation, and did this in such a way that her works promoted the classical literature along with the classical values.
Keywords: sociological and sociocultural method; philosophical determinism; autonomy of a work of art; artistic worldview; classics; values; interpretive community